Шляхи вдосконалення аутсорсингових послуг сервісних ремонтних служб промислового підприємства - Передрій, Андреа Елізабет Юріївна (НТУ "ХПІ", 2018)
Стаття присвячена розкриттю комплексу питань, пов'язаних з оцінкою ефективності передачі на аутсорсинг сервісних ремонтних служб великого промислового підприємства. Актуальність такого механізму в українській економіці пов'язана з тим, що утримання власного ремонтного господарства на великих промислових підприємствах є вагомим фактором зниження його прибутку. Організація сервісної ремонтної служби відкриває широкі перспективи підвищення ефективності виробництва та підвищення якості продукції, яка випускається.

The article is devoted to the disclosure of a set of issues related to the assessment of the efficiency of outsourcing the service repair services of a large industrial enterprise. The relevance of such a mechanism in the Ukrainian economy is due to the fact that the maintenance of own repair facilities at large industrial enterprises is a significant factor in reducing it. The analysis of existing approaches to the organization and planning of maintenance and repair of equipment, identifying factors that determine the efficiency of the transfer of these works from the parent company outsourcing. In the transition to outsourcing the first main task - the choice of the optimal model of service organization in the enterprise. The organization of a service repair unit opens up broad prospects for improving the efficiency of production and improving the quality of products. The service provider may also affect the quality of the final product, in part expanding its boundaries, requirements and change control, having more qualified and experienced staff.
Ways of improving outsourcing service of service repair services of an industrial enterprise
Keywords: виробництво; сервіс; ремонт; ефективність діяльності підприємства; планово-діагностичне обслуговування; production; efficiency of the enterprise